PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN DAN REPUTASI KAP TERHADAP AUDIT DELAY: (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2018-2020) - Dika Karlinda Sari; A.Khoirun Nisa (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2022)
This study aims to determine the effect of Profitability, Solvabilitas, Firm Size and Reputation of KAP on Audit Delay. The sample used in this study are manufacturing companies listed on the Indonesia Stock Exchange from 2018-2020. The number of samples obtained is 61 companies that have been determined using purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The test results show that the profitability, solvency and reputation of KAP have an effect on audit delay, while the firm size variable has no effect on audit delay.